COMPARATIVE ANALYSIS OF SPECIAL AUTONOMY FUND UTILIZATION: EVIDENCE FROM ACEH AND PAPUA - Zahrah Inayah (GLOBAL RESEARCH IN ECONOMICS AND ADVANCE THEORY (GREAT), 2026)
This study advances the literature on asymmetric fiscal decentralization by providing a systematic comparative analysis of Special Autonomy Fund (SAF) utilization in Aceh and Papua, two conflict-affected regions in Indonesia that share similar fiscal privileges but exhibit markedly different development trajectories. Unlike prior studies that predominantly assess SAF impacts in a single-region or sector-specific context, this research introduces a cross-regional institutional comparison that explicitly links fund effectiveness to variations in governance quality, accountability mechanisms, and post-conflict political stability. Employing a mixed-methods approach that combines quantitative analysis of fiscal transfers and socio-economic indicators with qualitative assessment of governance arrangements, the study reveals that Aceh’s relatively stronger institutional capacity, participatory governance, and transparency mechanisms enable SAF to translate into tangible improvements in poverty reduction and human development. In contrast, Papua’s weaker administrative capacity and limited public oversight significantly constrain the developmental returns of comparable fiscal transfers. The study’s key novelty lies in demonstrating that special autonomy funds function not as neutral fiscal instruments but as institution-contingent policy tools whose effectiveness is conditional upon local governance structures and social capital. By reframing SAF as an institutional rather than purely fiscal intervention, this research contributes new empirical and conceptual insights to the decentralization and post-conflict governance literature, offering policy-relevant lessons for the design of asymmetric autonomy frameworks in heterogeneous and politically sensitive regions.